2011
DOI: 10.1002/anie.201101191
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed Cross‐Coupling of Styrenyl Epoxides with Boronic Acids

Abstract: Let's get multicatalytic! A Ni0 catalyst complexed with a biaryldialkyl monophosphine ligand facilitates CC bond formation between styrenyl epoxides and aryl boronic acids (see scheme). X‐ray analysis of a catalytically active nickel/ligand complex supports a redox pathway involving C sp 3O bond activation. A variety of α‐substituted alcohols were generated with good reaction efficiency by a multicatalytic sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(73 citation statements)
references
References 68 publications
2
71
0
Order By: Relevance
“…9 Doyle reported a nickel-catalyzed coupling with arylboronic acids that formed rearranged products 4 , 10 similar to related reactions with allylmetal reagents. 11 While Flowers and Gansäuer recently extended Ti(III)-epoxide chemistry 12 to the intra-molecular, internal arylation of epoxides, 13 the intermolecular arylation of epoxides to form products 2 and 3 remains limited to traditional methods.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…9 Doyle reported a nickel-catalyzed coupling with arylboronic acids that formed rearranged products 4 , 10 similar to related reactions with allylmetal reagents. 11 While Flowers and Gansäuer recently extended Ti(III)-epoxide chemistry 12 to the intra-molecular, internal arylation of epoxides, 13 the intermolecular arylation of epoxides to form products 2 and 3 remains limited to traditional methods.…”
mentioning
confidence: 81%
“…Stronger acids (DABCO•2HCl, 2,4,6-collidine•HCl) and weaker acids (DBU•HCl) provided no cross product. 20 Even though nickel is known to isomerize epoxides to aldehydes, 10, 21 no rearranged products ( 4 ) were observed.…”
mentioning
confidence: 99%
“…19 We recently reported Suzuki–Miyaura reactions of quinoline-derived N,O- acetals 20 and styrenyl epoxides. 21 Our preliminary mechanistic data indicated that in these systems C sp 3 –O oxidative addition is promoted by Lewis acid complexation of the boronic acid to the Lewis basic oxygen of the electrophile. Inspired by these findings, we decided to pursue the possibility that boronic acid activation 22 of an allylic acetal in the absence of a base would encourage selective oxidative addition and transmetalation.…”
mentioning
confidence: 84%
“…5 C-C bond formation with dearomatization was also observed for a nickel biphenyl phosphine complex. 6 The common property of these species is interaction of the metal center with arene leading to activation toward attack of the π-system. Herein, we present a rare example of C-H to C-P conversion with a mechanism for C-H functionalization unusual for group 10 metals, involving metal(II) activation of an arene π-system toward attack by a nucleophile (Figure 1c).…”
mentioning
confidence: 99%
“…To our knowledge, this is the first example of such a mechanism mediated by Ni II and Pd II without involving the formation of σ-complex or strong metal arene bonds (Scheme 1). Previously reported transition-metal-mediated dearomatization reactions via nucleophilic attack have been limited to d 6 -complexes such as ( η 6 -arene)Cr(CO) 3 and [( η 6 -arene)Mn(CO) 3 ] + . 3,13 Rearomatization of the arene requires the presence of an anionic leaving group or stoichiometric chemical oxidation and metal loss, which has hindered the development of catalytic versions (Figure 1).…”
mentioning
confidence: 99%